(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
A 20-year-old male presented with a small swelling in the vestibular area of the right lower second mandibular molar region. Clinically, the area was slightly tender and the tooth had grade two mobility. There was no nerve deficit or adenopathy in the head and neck. Vitality testing of the tooth revealed the tooth to be vital. Radiographically, the tooth had a relativelydefined radiolucent lesion in the periapex with resorption of the mesial and distal root apices. We have discussed the probable treatment plan with the patient and going for extraction of involving tooth and excision of whole lesion with complete margin which is suspected as ameloblastoma. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12031 Bangladesh J Otorhinolaryngol 2012; 18(2): 238-241